Peran Sarana-Prasarana dalam Peningkatkan Mutu Pendidikan di Madrasah Aliyah Pembangunan UIN Syarif Hidayatullah Jakarta - Aminusyai, Achmad Fachrurozi; Ta’rifin, Ahmad; Fitrianingsih, Sri Eka; Istiqomah, Nurul; Azizah, Nikmatul; Nida, Khoirun (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This research was conducted at MA Pembangunan UIN Syarif Hidayatullah Jakarta, aiming to identify the condition and role of facilities and infrastructure in improving the quality of education at Madrasah Aliyah (MA) Pembangunan UIN Syarif Hidayatullah. The method used is descriptive qualitative, including field surveys, interviews with stakeholders, and analysis of data from various sources. The results show that the availability of adequate facilities and infrastructure has a positive correlation with improving the quality of learning and the ability of students to achieve a proper and technology-based education. This study concludes that investment in facilities and infrastructure development should be prioritized by schools to improve educational progress. Recommendations include increased budgets, comprehensive planning and community involvement in the development process to ensure local needs are met and sustainability is assured.